Oxidative cyanation of tertiary amines for facile synthesis of tetrahydroisoquinolines with quaternary centers. (9th November 2022) - Ji, Yue; Zhang, Xue; Wu, Ya; Dang, Ze-Lin; Han, Wei-Wei; Wang, Si-Chang; Dong, San-Bao; Zhang, Qun-Zheng
Graphical abstract: Abstract: A facile and efficient synthesis of tetrahydroisoquinolines with quaternary centers has been successfully realized by orchestrating a sequential process consisted of N -bromosuccinimide oxidation and cyanation of tertiary amines. This compatible combination protocol enables one-pot synthesis of α-cyano tetrahydroisoquinolines containing a quaternary center with up to 99% yield.